LANGKAH-LANGKAH STRATEGIS MEMBERANTAS KORUPSI DI INDONESIA - Benny K.Harman; Antonius Sudirman (Masalah-Masalah Hukum, 2011)
This writing speaks of strategic steps in eradicating the corruption in Indonesia. The out come of the discussions shows that there is a need for strategic steps to eradicate the corruption in Indonesia they are as follow: (1) There is the social movement to do ,t. (2) Po/Jt,cal networking to strengthen the ant1-corrupt1on movements; (3}The commitment of the P.Olfilcal party to eradicate the corruption; (4) To reform the anti-corruption law so that criminal sanctions are to prevent a person committing corruption; ( 5) Team working of law enforcer to investigate and prosecute for corruption; (6) People's supervision toward the apparatuses: (7) To increase the public service and to implement of good governance and clean government.